Thermal penetration depth enhancement in latent heat thermal energy storage system in the presence of heat pipe based on both charging and discharging processes. (15th September 2017) - Lohrasbi, Sina; Gorji-Bandpy, Mofid; Ganji, Davood Domiri
Highlights: LHTESS is studied from the viewpoint of both charging and discharging processes. V-shaped fin is employed to improve heat pipe ability in spreading heat into the PCM. Fin configuration is optimized using RSM and CFD techniques simultaneously. The optimized V-shaped fin is attached to heat pipe and immersed into the LHTESS. The efficiency of optimized system is compared to other conventional systems. Abstract: Latent Heat Thermal Energy Storage Systems (LHTESS) have attracted increasing attentions in recent years. In these systems, energy storage-retrieval are achieved during solid-liquid phase change of Phase Change Materials (PCM). Because of low thermal conductivity of PCMs, energy storage and retrieval cannot be achieved in desired time duration. In the present study, a novel fin configuration is optimized based on both charging and discharging processes using Response Surface Method (RSM). Following this, the optimum fin array is attached to heat pipe to improve its ability in increasing thermal penetration depth into the PCM. In the subsequent stage, the system with optimum finned heat pipe is compared to other systems in the presence of common fin arrays. The parameter of maximum energy storage capacity of the system is implemented quantitatively in the optimization procedure, and the efficiency of using this parameter as one of the objectives of LHTESS design is examined, which is proposed as the novelty here. Results indicate that attaching fin of suitable configuration to the heat pipe enhances its performance in increasing thermal penetration depth into the PCM. Moreover, it is indicated that choosing maximum energy storage capacity as one of the objectives of optimization procedure for LHTESS performance evaluation leads to efficient design.